The Impact of Experiential Learning on Student’s Knowledge - Shinta Futichatul ‘Aini; Nanda Zeni Arumsari; Hani Fitria Sari; Umi Rachmawati (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
The purpose of this study is to find out how the influence of the use of experiential learning modelsas a means of increasing student’s knowledge in the Covid-19 pandemic. This research uses ClassAction Research (PTK) with a quantitative approach. The subjects in the study were 5th graderstotaling 22 children. But the authors only sampled 10 children due to the current pandemicsituation, which does not allow the authors to gather all the children in one class. Authors useessay tests to measure students' abilities. The average Cycle 1 score that students get is 71.5 andthe average Cycle 2 score that students get is 86.5. There is a significant increase in value afterand before the study using experiential learning models. The results of this study show that theExperiential Learning model has a positive effect on student’s knowledge.